Tata Kelola Pembuatan Laporan Penerimaan Harian Keuangan di PT Gala Bumiperkasa (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
Abstracts for each article are written in Indonesian and English. Abstract forms are written in a concise and clear manner describing the background, methods, results, conclusions, and suggestions (implications) of the research. The names of the authors are recommended to be written in full, or if they are too long can be abbreviated as their middle names. While the first and last names are not abbreviated. Use spaces to separate the initials of the author. Not allowed to write references / citations in abstracts. Abstract length must be between 150 - 250 words. Progress in the digital era or digitalization has had a significant impact on human life. The development of the digital world has also resulted in changes to human employment regulations, including in the field of accounting. Technological advances have created many applications that make things easier and can improve the work efficiency of employees and the business world. The era of digitalization is also utilized in financial management at PT Gala Bumi Perkasa. This article or writing aims to provide information regarding the governance of making daily financial receipt reports at PT Gala BumiPerkasa. The problem focuses on how PT Gala BumiPerkasa as the manager of Pasar Turi Baru manages the preparation of daily financial receipt reports. In order to approach this problem, Kuswadi's theoretical reference regarding the four basic frameworks of financial management is used, namely planning, recording, reporting and controlling. Data was collected through interviews and direct observation and analyzed qualitatively. This research concludes that the management of making and recording daily receipt reports at PT Gala BumiPerkasa is system-based and complies with accounting standards. Adequate human resources and digitalization in managing daily revenue reports increase efficiency in presenting financial information. However, there are limitations in financial management based on this system at PT Gala Bumi Perkasa because it still provides cash payments and errors often occur in the system.
Keywords: Indonesian